Downregulated miRNA-491-3p accelerates colorectal cancer growth by increasing uMtCK expression - Xingkui Tang; Yukun Lin; Jialin He; Xijun Luo; Junjie Liang; Xianjun Zhu (PeerJ, 2022)
Colorectal carcinoma (CRC) is the second most frequent cancer worldwide. MiR-491-3p, a tumor-suppressive microRNA (miRNA, miR), has been revealed to be abnormally expressed in CRC tissues. Meanwhile, up-regulated ubiquitous mitochondrial creatine kinase (uMtCK) contributes to CRC cell proliferation. Here we aim to explore whether aberrant miR-491-3p expression promotes CRC progression through regulating uMtCK. To this end, miR-491-3p and uMtCK levels were assessed in CRC tissues using quantitative real-time PCR (qRT-PCR). The biological roles of miR-491-3p and uMtCK in regulating CRC growth were evaluated using colony formation assay and mouse Xenograft tumour model. We found that miR-491-3p expression was decreased in CRC tissues compared with matched para-cancerous tissues, whereas uMtCK expression was increased. Functionally, miR-491-3p overexpression repressed SW480 cell growth, whereas miR-491-3p depletion accelerated SW620 cell proliferation and growth. Inversely, uMtCK positively regulated CRC cell proliferation. Mechanistically, miR-491-3p post-transcriptionally downregulated uMtCK expression by binding to 3’-UTR of uMtCK. Consequently, restoring uMtCK expression markedly eliminated the role of miR-491-3p in suppressing CRC growth. Collectively, miR-491-3p functions as a tumour suppressor gene by repressing uMtCK, and may be a potential target for CRC treatment.